Bioconversion of Palm Oil into Biosurfactant by Halomonas meridiana BK-AB4 for the Application of Corrosion Inhibitor - Ira Prima Sari; Muhammad Imam Basyiruddin; Rukman Hertadi (Indonesian Journal of Chemistry, 2018)
Biosurfactant is environmentally friendly surfactant produced by a certain microorganism in a lipid-rich medium. A previous study has shown that Halomonas meridiana BK-AB4 had the potential of a moderately halophilic bacterium in converting olive oil into biosurfactant. In the present study, the effect of changing the carbon source from olive oil into cheaper and more abundant vegetable oil, which is palm oil, for the production of the biosurfactant was evaluated. The study began by optimizing the production medium with varying the nitrogen source, the concentration of palm oil and pH. The optimum condition of biosurfactant production was observed in the medium consisted of 0.6% (w/v) of urea, 2% (v/v) of palm oil and pH 9. The resulted biosurfactant was stable at pH 7–10 and in the salt concentration of 6–15%. Biosurfactant activity in lowering air-water surface tension was measured using the Du Noüy ring method, and the value of critical micelle concentration (CMC) was about 233 ppm. At this point, the surface tension of water dropped from 68.3 to 49.8 dyne/cm. Preliminary structural analysis by using FTIR technique suggested that the resulted biosurfactant has -OH, -C-H aliphatic C=C, H-C-C and C=O groups in its structure, which is similar to that of the fatty-acid type of biosurfactant. The potential of biosurfactant as a metal corrosion inhibitor was evaluated by using electrochemical impedance spectroscopy (EIS) that measured at 30 °C. The measurement revealed that the highest inhibition level was observed at the biosurfactant concentration about 200 ppm that corresponds to the inhibition level about 53.23%.